Implementation of Religion and Astronomy for Children Through the Reggio Emillia Learning Model - Tunas, Rosi; Amalia Rabiatul Adwiah; Maemonah (Jurnal Pedagogi dan Pembelajaran, 2023)
Developing religion and science in early childhood requires the right stimulation to develop optimally. This study aims to analyze the influence exerted by the Reggio Emilia learning model in developing religion and the science of astronomy in children. This research belongs to the quantitative research in quasi-experimental using the posttest-only control group design. The population in this study were 18 early childhood children aged 5-6 years. Sampling was done using a saturated sample technique, in which all population members were used as research samples. Data collection in this study was carried out using non-test methods in the form of observation, interviews, and questionnaires. The research instrument used was in the form of children's religious and scientific ability instruments. The data obtained in the study were then analyzed using quantitative descriptive analysis techniques through validity testing, reliability testing, normality testing, and hypothesis testing. The results of the data analysis show that the calculated f value is 3.789 and a significance value of 0.007. The hypothesis is accepted by the results obtained with the sig <0.05 and f count > f table; this study has a sig value of 0.007 <0.05 and f count of 3.789> 3.63. Based on these results, the Reggio Emilia learning model positively and significantly influences astronomy's religious and scientific values in early childhood.